Forecasting Urban Water Demand in 2032: A Case Study of Bandung City - Baseham, Abdullah (Fakultas Teknik, Universitas Brawijaya, 2024)
This research confronts the pressing challenge of escalating clean water demand in Bandung, a dynamically expanding metropolitan city in Indonesia's West Java Province. Drawing on secondary data from the Central Bureau of Statistics and other relevant literature, the study leverages Microsoft Excel to perform a dual analysis: forecasting population growth and calculating future water demand through 2032. A pivotal outcome reveals that the existing water supply infrastructure in Bandung will be woefully insufficient to meet the exponentially growing clean water requirements. Uniquely, this study employs multiple forecasting methodologies, adding depth and reliability to the projections. It there by offers new, essential insights into the quantifiable volume of water that will be needed to sustain future urban development. The research argues that current supply-focused water management strategies are inherently flawed and calls for an immediate paradigm shift toward demand-side management to mitigate the impending water crisis. Specific recommendations include the incorporation of alternative water sources such as rainwater harvesting and groundwater recharge. Moreover, the study emphasizes the need for rapid governmental action, including policy revision and public education campaigns, to ensure water sustainability. This research stands as a critical resource for policymakers, urban planners, and water management experts aiming to bridge the looming water supply-demand gap in Bandung.